Optimisation of milling parameters during mechanical activation for direct synthesis of hydroxyapatite. - Othman, Radzali (Asean Engineering Journal)
Mechanical activation is one of the methods to synthesize a single-phase hydroxyapatite. In this work, hydroxyapatite was directly synthesized by mechanical milling in a planetary ball mill, using calcium phospate dibasic dihydrate, CaHPO4.2H2O, and calcium hydroxide, Ca(OH)2, as the precursors or raw materials. The milling parameters investigated included the duration of milling, the milling media, and the ball-to-powder ratio (BPR). The results thus far indicated that the parameters of milling can be optimised down to 2 hours of milling duration, using either stainless steel or agate milling media, and a BPR of 10:1. The optimization was confirmed principally by x-ray diffraction (XRD) which indicated that only single-phase hydroxyapatite was the final product in this milling reaction. Other characterization methods employed were scanning electron microscopy (SEM), transmission electron microscopy (TEM) and particle size analysis. Characterization by SEM and TEM showed that the morphologies of the hydroxyapatite particles are needle-shaped and the sizes are dependent on the changes in the parameters used in the mechanical activation milling process.